A student-led curriculum framework for homeless and vulnerably housed populations - Hashmi, Syeda S; Saad, Ammar; Leps, Caroline; Gillies-Podgorecki, Jamie; Feeney, Brandon; Hardy, Courtney; Falzone, Nicole; Archibald, Doug; Hoang, Tuan; Bond, Andrew; Wang, Jean; Alkhateeb, Qasem; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Medical student demands for competency based homeless health education is increasing. Indeed, humans living homeless is a treatable health and social emergency. This innovation report outlines the initial development of an education framework for homeless health. Methods A medical student task force and educators conducted a mixed method study, including a scoping review of homeless health curriculum and competencies, a cross-country survey of medical students, and unique clinical guidelines. The task force collaborated with persons with lived experience and clinical guideline developers from the Homeless Health Research Network. The students presented at the Toronto Homeless Health Summit and refined the framework with feedback from homeless health experts. Results The main outcome was an evidence-based Homeless Health Curriculum Framework. It uses seven core competencies; with communication, advocacy, leadership, and upstream approaches playing the strongest roles. The framework integrated the new clinical guideline (housing, income assistance, case management and addiction). In addition, it identified approaches to support mental health care with trauma informed and patient centered care. It identified public health values, clinical objectives, and case studies. The framework aims to inform the design, delivery, service learning and evaluation for medical school curriculum. Conclusions This student-led curriculum framework can support the design, implementation, delivery and evaluation of homeless health within the undergraduate medical curriculum. The framework can lay the foundation for new doctors, research and development; support consistency across programs; and support the creation of national learning and evaluation tools.